Designing and making a difference: an exploration of technology education for rural school teachers - SchÃ¤fer, Marc (Rhodes University, Faculty of Education, Department of Education, 2000)
This qualitative study focused on a Technology Education programme for farm school teachers in the Eastern Cape province of South Africa. These teachers were faced with the challenge of incorporating Technology Education into their curriculum. The study was conducted within the context of an investigation into the conceptual nature of technology and an exploration of the theoretical underpinnings of Technology Education within both the international and South African context. Technology Education is being introduced into the South African curriculum against a background of educational transformation and the building of capacity to solve real life problems. This calls for a curriculum that will empower learners to be innovative, creative and skilled problem solvers. The introduction and incorporation of Technoiogy Education into the school curriculum poses a formidable challenge to farm schools in particular. Their unique history of neglect and legacy of underqualified teachers has made the introduction of any curriculum innovation process very difficult and challenging. This study analyses how an introductory Technology Education programme for farm school teachers in the Winterberg area of the Eastern Cape impacted~ on the teachers' professional and personal lives. It shows the importance of developing teclpological skills in conjunction with life skills in cO.ntributing to the empowerment, both in the work place and in the wider context, of rural school teachers. It highlights the need for supportive in-service education programmes and strengthens the argument for an integrative and mulitidisciplinary approach to the introduction of Technology Education in farm schools. Data was collected by means of questionnaires, interviews and photographs.
Keywords: Technology -- Study and teaching -- South Africa -- Eastern Cape; Technology -- Study and teaching -- South Africa; Rural schools -- South Africa -- Eastern Cape; Education, Rural -- South Africa; Winterberg schools trust